Integration of Spiritual Values in the Curriculum of Islamic Boarding Schools: A Case Study of the Effectiveness of the Jami'atul Muballighah Program in Increasing the Spiritual Intelligence of Students - Shafa MF (Al-Qalam Institute, 2024)
This research focuses on evaluating the effectiveness of the Jami'atul Muballighah Program in improving the spiritual intelligence of students at the At-Taufiqiyah Islamic Boarding School. The main objective of this study is to identify the key factors that contribute to the success of the program and how the program is implemented effectively to develop the spiritual character of the students. The research method used is a qualitative approach with a case study type, where data is collected through in-depth interviews, participatory observations, and documentation studies. The results of the study show that the selection of relevant materials, comprehensive management training, and the implementation of structured activities consistently are the main factors in improving the spiritual intelligence of students. The implications of this study show that a holistic and participatory approach in the management of spiritual education programs can be adopted by other pesantren to strengthen the character education of students